Factors influencing women's health in developing African countries - Valerie Janet Ehlers (AOSIS, 1999)
In Sub-Sahara Africa, women perform 80 of the agricultural labour. Opsomming In Sub-Sahara Afrika verrig vrouens 80 van die landbou arbeid. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.